Constructing Competition Law in China: The Potential Value of European and U.S. Experience - David J. Gerber (Washington University Global Studies Law Review, 2004)
In this brief Essay, I examine several of the key decisions to be made in constructing a competition law for China and consider ways in which foreign experience may be of value to Chinese decision-makers.
Keywords: Antitrust law; Competition (Economics); China; European Union; United States